New drugs are not enough-drug repositioning in oncology: An update - Armando, Romina Gabriela (2020)
Drug repositioning refers to the concept of discovering novel clinical benefits of drugs that are already known for use treating other diseases. The advantages of this are that several important drug characteristics are already established (including efficacy, pharmacokinetics, pharmacodynamics and toxicity), making the process of research for a putative drug quicker and less costly. Drug repositioning in oncology has received extensive focus. The present review summarizes the most prominent examples of drug repositioning for the treatment of cancer, taking into consideration their primary use, proposed anticancer mechanisms and current development status.